x y + y z = y z + x z = x z + y x = x 2 + y 2 + z 2 = 3 5 3 2 2 7 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can simplify your work by a bit.
Hint: Add up the first three equations together.
Thanks. Yes, it is simpler. Edited.
First time writing a solution.. Hope this helps
Let (i) xy + yz = 35 (ii) yz + xz = 32 (iii) xz + yx = 27
Calculate (i) - (ii) + (iii) = (xy - xz) + (xz + yx) = 2xy = 30 xy = 15
(ii) - (iii) + (i) = (yz - yx) + (xy + yz) = 2yz = 40 yz = 20
(iii) - (i) + (ii) = (xz - yz) + (yz + xz) = 2xz = 24 xz = 12
By inserting x = 15/y and y = 20/z, you get z = 4
Then xz = 12 so x = 3
And xy = 15 so y = 5
Therefore, x^2 + y^2 + z^2 = 9 + 25 + 16
= 50
Good solution
The sum of 3 5 + 3 2 + 2 7 = 9 4 , which is 2 ( x y + y z + x z ) .
x y + y z + x z = 2 9 4 = 4 7
x z = 4 7 − 3 5 = 1 2
x y = 4 7 − 3 2 = 1 5
y z = 4 7 − 2 7 = 2 0
H C F ( 1 2 , 1 5 ) = 3
H C F ( 1 2 , 2 0 ) = 4
H C F ( 2 0 , 1 5 ) = 5
3 2 + 4 2 + 5 2 = 5 0
What is the relevance of HCF to this question? The question did not explicitly state that x , y , z are integers.
xy+ yz= 35...(1)
yz+ xz= 32...(2)
xz+ yx= 27...(3)
((1)+ (2)+ (3))/ 2...xy+ yz+ zx= 47..(4)
(4)- (1)...zx= 12...(5)
(4)- (2)...yx= 15...(6)
(4)- (3)...yz= 20...(7)
(5)* (6)* (7)...(xyz)^2= 12* 15* 20...or (xyz)= 3
4
5...(8)
(8)/ (5)...y= 5
(8)/ (6)...z= 4
(8)/ (7...x= 3
so...x^2+ y^2+ z^2= 9+ 25+ 16= 50
Problem Loading...
Note Loading...
Set Loading...
⎩ ⎪ ⎨ ⎪ ⎧ x y + y z = 3 5 y z + z x = 3 2 z x + x y = 2 7 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
⇒ ⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ ( 1 ) + ( 2 ) + ( 3 ) : ( 4 ) − ( 1 ) : ( 4 ) − ( 2 ) : ( 4 ) − ( 3 ) : 2 ( x y + y z + z x ) = 9 4 ⇒ x y + y z + z x = 4 7 z x = 4 7 − 3 5 = 1 2 x y = 4 7 − 3 2 = 1 5 y z = 4 7 − 2 7 = 2 0 . . . ( 4 ) . . . ( 5 ) . . . ( 6 ) . . . ( 7 )
⇒ ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ ( 7 ) ( 6 ) × ( 5 ) : ( 6 ) : ( 5 ) : y z x y × z x = 2 0 1 5 × 1 2 ± 3 y = 1 5 ± 3 z = 1 2 ⇒ x 2 = 9 ⇒ y = ± 5 ⇒ z = ± 4 ⇒ x = ± 3
⇒ x 2 + y 2 + z 2 = 9 + 2 5 + 1 6 = 5 0